Foreign Investment and the Battle for Fair Competition: Assessing the Gaps in Indonesia’s Mineral Mining Regulations - Agus Lanini; Sitti Fatimah Maddusila; Izan Mateo Cassandro (Journal of Indonesian Legal Studies, 2026)
Foreign investment in Indonesia’s mineral and coal mining sector has surged significantly, driven by growing global demand and the country’s strategic resource position, particularly amid the energy transition. However, this influx exposes two critical challenges. First, the investment regulatory framework remains fragmented and inconsistent, creating loopholes that enable foreign investors to dominate strategic national resources without sufficient safeguards for domestic stakeholders. Second, weak enforcement of competition law fosters unfair business practices, including cartel formation, abuse of dominant positions, collusive tendering, and regulatory manipulation through undue influence on public officials. These practices undermine fair competition, harm local enterprises, reduce state revenue, and threaten environmental sustainability. This study critically examines the gaps in Indonesia’s investment and competition legal frameworks and their interaction within the mining sector. Using a normative and comparative legal analysis, it reveals how governance weaknesses perpetuate imbalances in the business relationships between foreign and domestic actors. The principal contribution lies in proposing a legal policy reform agenda aimed at balancing the imperative of attracting foreign capital with ensuring equitable competition and responsible resource management. Recommendations emphasize regulatory harmonization, institutional strengthening, and the implementation of effective sanctions to foster a transparent, fair, and sustainable investment climate. This research is timely given Indonesia’s pivotal role in the global mineral supply chain and its commitment to sustainable development.